Kierunki zmian na rynku żywnościowym w Polsce - Szwacka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
The article contains the analysis of the changes occurring in the patterns of human behaviour on food market in Poland. The hierarchy of the factors influencing demand and the most important tendencies on the world market have been established, as well as their implications for modelling Polish food market. Furthermore the proposals of the patterns of human behaviour (basing on unifi cation and diversification) on European food market have been described.